Distribution of Ocular Component Measures and Refraction in Brazilian School Children. (2nd January 2017) - Lira, Rodrigo Pessoa Cavalcanti; Arieta, Carlos Eduardo Leite; Passos, Thaís Helena Moreira; Maziero, Diana; Astur, Gustavo Lima do Valle; do Espírito Santo, Ítalo Fernandes; Bertolani, Ana Cláudia; Pozzi, Luis Fernando; de Castro, Rosane Silvestre; Ferraz, Álvaro Antônio Bandeira
ABSTRACT: Purpose : To describe ocular component values and refraction in 6–17-year-old school children in Campinas, Brazil. Methods : To obtain a representative sample, a total of 1100 6–17-year-old public school students in Campinas, Brazil, were randomly selected and divided into groups according to median ages 6 years (range 5–7 years), 10 years (range 9–11 years), 14 years (range 13–15 years), and 17 years (range 16–18 years). Cycloplegic autorefraction and ocular biometry were performed on each child. Results : Parental consent for participation was obtained for 778 of the 1100 students (70.7%). Of these, 440 (56.6%) were female and 330 (44.4%) male. Sex distributions were similar for each median age group. Median age groups 6, 10, 14, and 17 years displayed significant trends of decreasing mean spherical equivalent refraction (SER; 0.96, 0.89, 0.57, and 0.23 diopters, D, respectively), mean lens thickness (3.50, 3.42, 3.41, and 3.45 mm, respectively), and mean lens power (23.6, 22.7, 21.8, and 21.2D, respectively), but significant trends of increasing mean anterior chamber depth (ACD; 3.00, 3.12, 3.16, and 3.15 mm, respectively), mean vitreous chamber depth (VCD; 16.0, 16.4, 16.6, and 16.8 mm, respectively), and mean axial length (22.5, 23.0, 23.2, 23.4 mm, respectively; all p for trend <0.001). Conclusions : Significant trends towards lower refractive power, increased prevalence of myopia, increased ACD, VCD, and axial length, and decreased lens power were associated with increasing age in these children. There were no significant changes in corneal thickness or corneal curvature.